2016
DOI: 10.1177/1471301216682626
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of home-based care for persons with dementia from formal and family caregivers’ perspective

Abstract: Western health care policy emphasizes continuity of care for people with dementia. This paper presents formal and family caregivers' descriptions of collaboration in home-based dementia care and explores whether this collaboration inhibits or enables continuity of care and the use of the statutory individual plan. Empirical data were derived from eighteen indepth interviews with formal and family caregivers and brief fieldwork. The results reveal dynamic positions in collaborative practice and, from these posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
(38 reference statements)
0
21
0
1
Order By: Relevance
“…Therefore, ensuring that the staff has sufficient knowledge about dementia may be important for customized service [25,26]. This can contribute to good quality of care [27,28] and better communication and cooperation between people with dementia and staff [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ensuring that the staff has sufficient knowledge about dementia may be important for customized service [25,26]. This can contribute to good quality of care [27,28] and better communication and cooperation between people with dementia and staff [7].…”
Section: Discussionmentioning
confidence: 99%
“…The findings in the current study might indicate that some people with dementia accept the care and support they receive as passive recipients with an overall desire to be satisfied with the service. Previous research has identified that care and support from home care services are described as standardized and based on routines that focus on practical tasks, and this can result in limited individualization to the patient's needs [24,27,28]. Furthermore, the communication between staff and the person with dementia during visits can become taskoriented [15,25].…”
Section: Low Expectations and Adapting To The Home Care Service Receivedmentioning
confidence: 99%
“…The need for coordination, planning and organization of the homecare service can exceed the capacity the service has to adapt to the individual patient (Fjørtoft et al., 2020). This may explain why homecare services have traditionally been minimally specialized and adapted to people with dementia (Bokberg et al., 2015) and have been described as providing the same type of help to most patients (Bokberg et al., 2015; Larsen et al., 2019; Turjamaa et al., 2014). Although the complexity experienced by the staff can be challenging, the need for a tailored service for people with dementia is emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Research into the continuity of care for such individuals living at home is scant (Larsen et al, 2019), and so the present study has added to this literature and highlighted the importance of meaningful interaction between the person with dementia and their carer, which was highly valued by families. This was vital and should not solely focus on the functional aspects of care, allowing for communication and connection at a meaningful level.…”
Section: Discussionmentioning
confidence: 94%